Spontaneous Uterine Rupture in a Greyhound Bitch during Parturition - Chul-Ho Park; Ki-Seok Oh; Chang-Ho Son (The Korean Society of Animal Reproduction and Biotechnology, 2014)
A 6-year old, Greyhound bitch was presented with vaginal hemorrhage and dystocia. Physical examination revealed severe vaginal hemorrhage, abdominal pain, pale mucous membranes and the presence of solid structures to abdominal palpation. A hematological test revealed a marked hemorrhagic anemia, and abdominal radiography and ultrasonographic examination showed two dead fetuses in the uterus. Median laparotomy revealed a rupture of the left uterine horn adjacent to the bifurcation, region of weakened uterine wall in the right uterine horn, blood clots and uterine fluids in abdominal cavity without septic peritonitis. The bitch underwent ovariohysterectomy and recovered without complication.